Application of a Seat-based Booking Control Mechanism in Rail Transport with Customer Diversion - Bulum, A. Z.; Dugenci, M.; Ipek, M. (Engineering, Technology & Applied Science Research, 2022)
The ticket booking control mechanism is a part of the Revenue Management (RM), commonly used in the airline industry. This study aims to optimize seat allocation in the railway industry and compare the performance of three booking control techniques by considering customer behavior. The preferences of customers who cannot find their desired ticket are considered as a customer diversion matrix, which also includes waiting and no-purchase probability. Α Ticket Booking System (TBS) with buckets, which assigns seats to buckets, was adapted and implemented on the Turkish railway for the first time. A genetic algorithm that is specifically written to apply the TBS, including customer diversion, is used in simulations to obtain approximate solutions. It is seen that TBS gave successful results with a revenue increase of around 5.8%. We can also suggest, considering customer behavior, that the revenue can be raised by sales in periods.